Ion Exchange/Insertion Reactions for Fabrication of Efficient Methylammonium Tin Iodide Perovskite Solar Cells. Issue 9 (14th March 2020) - Wang, Pengcheng; Li, Fengzhu; Jiang, Ke‐Jian; Zhang, Yanyan; Fan, Haochen; Zhang, Yue; Miao, Yu; Huang, Jin‐Hua; Gao, Caiyan; Zhou, Xueqin; Wang, Fuyi; Yang, Lian‐Ming; et al.
Abstract: The low toxicity, narrow bandgaps, and high charge‐carrier mobilities make tin perovskites the most promising light absorbers for low‐cost perovskite solar cells (PSCs). However, the development of the Sn‐based PSCs is seriously hampered by the critical issues of poor stability and low power conversion efficiency (PCE) due to the facile oxidation of Sn 2+ to Sn 4+ and poor film formability of the perovskite films. Herein, a synthetic strategy is developed for the fabrication of methylammonium tin iodide (MASnI3 ) film via ion exchange/insertion reactions between solid‐state SnF2 and gaseous methylammonium iodide. In this way, the nucleation and crystallization of MASnI3 can be well controlled, and a highly uniform pinhole‐free MASnI3 perovskite film is obtained. More importantly, the detrimental oxidation can be effectively suppressed in the resulting MASnI3 film due to the presence of a large amount of remaining SnF2 . This high‐quality perovskite film enables the realization of a PCE of 7.78%, which is among the highest values reported for the MASnI3 ‐based solar cells. Moreover, the MASnI3 solar cells exhibit high reproducibility and good stability. This method provides new opportunities for the fabrication of low‐cost and lead‐free tin‐based halide perovskite solar cells. Abstract : Tin fluoride and methylammonium iodide are employed as precursors for the fabrication of methylammonium tin iodide (MASnI3 ) film via an ion exchange/insertion reactions approach, and a highly uniform, pinhole‐free perovskite film is obtained with a high concentration of SnF2 and a low content of Sn 4+ . The corresponding solar cell exhibits the highest power conversion efficiency of 7.78% with high reproducibility and stability.